Studi Yuridis Terhadap Kewenangan Militer Dalam Penanganan Bencana Alam di Indonesia - Lidowati, Alvina Maretia; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
Military comes from the word miles, meaning people who are ready or assigned to go to war. The military is a tool of the state that is assigned to go to war and defend the country. Legal politics in the current era or after the reform era states that those who commit general crimes must be subject to general justice. Therefore, in Indonesia itself, regulations are regulated regarding the formation of military justice in Indonesia. Referring to the country of Indonesia which is an agricultural country with a geographical area flanked by two continents and two oceans, Indonesia's position is very strategic because its territory is very potential. Although Indonesia has a potential area, Indonesia is very disadvantaged because it has a territory located in the ring of fire area. Thus, Indonesia becomes an area prone to natural disasters due to this. Therefore, the military also has a role to help overcome natural disasters because the military has the capacity in the form of the ability to carry out tasks which are in fact in emergency conditions with its command network down to the regional level. This is based on the fact that natural disaster management is not only the task of BNPB and BPBD according to the military, but this proves that the military can also help with problems related to natural disaster management